2-D multiparameter viscoelastic shallow-seismic full-waveform inversion: reconstruction tests and first field-data application. Issue 1 (27th April 2020) - Gao, Lingli; Pan, Yudi; Bohlen, Thomas
SUMMARY: 2-D full-waveform inversion (FWI) of shallow-seismic wavefields has recently become a novel way to reconstruct S -wave velocity models of the shallow subsurface with high vertical and lateral resolution. In most applications, seismic wave attenuation is ignored or considered as a passive modelling parameter only. In this study, we explore the feasibility and performance of multiparameter viscoelastic 2-D FWI in which seismic velocities and attenuation of P and S waves, respectively, and mass density are inverted simultaneously. Synthetic reconstruction experiments reveal that multiple crosstalks between all viscoelastic material parameters may occur. The reconstruction of S -wave velocity is always robust and of high quality. The parameters P -wave velocity and density exhibit weaker sensitivity and can be reconstructed more reliably by multiparameter viscoelastic FWI. Anomalies in S -wave attenuation can be recovered but with limited resolution. In a field-data application, a small-scale refilled trench is nicely delineated as a low P - and S -wave velocity anomaly. The reconstruction of P -wave velocity is improved by the simultaneous inversion of attenuation. The reconstructed S -wave attenuation reveals higher attenuation in the shallow weathering zone and weaker attenuation below. The variations in the reconstructed P - and S -wave velocity models are consistent with the reflectivity observed in a ground penetrating radar (GPR) profile.